The evolution of stage‐specific virulence: Differential selection of parasites in juveniles. Issue 2 (27th February 2019) - Iritani, Ryosuke; Visher, Elisa; Boots, Mike
Abstract: The impact of infectious disease is often very different in juveniles and adults, but theory has focused on the drivers of stage‐dependent defense in hosts rather than the potential for stage‐dependent virulence evolution in parasites. Stage structure has the potential to be important to the evolution of pathogens because it exposes parasites to heterogeneous environments in terms of both host characteristics and transmission pathways. We develop a stage‐structured (juvenile–adult) epidemiological model and examine the evolutionary outcomes of stage‐specific virulence under the classic assumption of a transmission‐virulence trade‐off. We show that selection on virulence against adults remains consistent with the classic theory. However, the evolution of juvenile virulence is sensitive to both demography and transmission pathway with higher virulence against juveniles being favored either when the transmission pathway is assortative (juveniles preferentially interact together) and the juvenile stage is long, or in contrast when the transmission pathway is disassortative and the juvenile stage is short. These results highlight the potentially profound effects of host stage structure on determining parasite virulence in nature. This new perspective may have broad implications for both understanding and managing disease severity.